Self-broadening coefficients in the ν2 +2ν3 band of 13CH4 at temperatures from 296 K to 200 K. (November 2020) - Sinitsa, L.N.; Serdyukov, V.I.; Scherbakov, A.P.; Baranovskaya, I.L.
Highlights: The spectrum of 13 CH4 studied between 7400 and 7600 cm −1 for the first time. Self-broadening parameters of 47 transitions of the ν2 +2ν3 band analyzed for the first time. Temperature exponent of self-broadening coefficients. Abstract: The 13 CH4 absorption spectra in the range between 7400 and 7600 cm −1 have been recorded at 4 temperatures from 296 K to 200 K using a Fourier transform spectrometer at pressures from 1 to 300 hPa, and at a 0.01 and 0.03 cm −1 spectral resolution. A 60 cm multipath cell with a path length of 1920 cm and a 220 long cm low temperature cell were used, which provided a threshold sensitivity to absorption of the order of 10 −6 cm −1 . The parameters of the Hartmann-Tran and Voigt lineshapes (line positions, intensities, self-broadening coefficients, self-shift coefficients and temperature dependences of the half width coefficients) were determined for the strongest transitions of the 13 CH4 ν2 +2ν3 band.